In situ immunomodulation of tumors with biosynthetic bacteria promote anti-tumor immunity - Zhongda Lin; Fanqiang Meng; Yumeng Ma; Chi Zhang; Zhirang Zhang; Zhaoxin Yang; Yuan Li; Linlin Hou; Yuzhong Xu; Xin Liang; Xudong Zhang (Bioactive Materials, 2024)
Immune checkpoint blockade (ICB) therapy potently revives T cell's response to cancer. However, patients suffered with tumors that had inadequate infiltrated immune cells only receive limited therapeutic benefits from ICB therapy. Synthetic biology promotes the alternative strategy of harnessing tumor-targeting bacteria to synthesize therapeutics to modulate immunity in situ. Herein, we engineered attenuated Salmonella typhimurium VNP20009 with gene circuits to synthetize granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin 7 (IL-7) within tumors, which recruited dendritic cells (DCs) and enhanced T cell priming to elicit anti-tumor response. The bacteria-produced GM-CSF stimulated the maturation of bone marrow-derived dendritic cells (BMDCs), while IL-7 promoted the proliferation of spleen isolated T cells and inhibited cytotoxicity T cell apoptosis in vitro. Virtually, engineered VNP20009 prefer to colonize in tumors, and inhibited tumor growth by enhancing DCs and T cell infiltration. Moreover, the tumor-toxic GZMB+ CD8+ T cell and IFN-γ+ CD8+ T cell populations conspicuously increased with the treatment of engineered bacteria. The combination of GM–CSF–IL-7-VNP20009 with PD-1 antibody synergistically stunted the tumor progress and metastasis.